Mg-substituted Prussian blue as a low-strain cathode material for aqueous Fe-ion batteries. Issue 27 (20th March 2023) - Huang, Ge; Lao, Zefeng; He, Ze; Xiong, Fangyu; Tan, Shuangshuang; Huang, Meng; Thompson, Greta; An, Qinyou; Mai, Liqiang
Abstract : We constructed a Mg-substituted Prussian blue analogue (MgFeHCF) as a low-strain cathode material for aqueous Fe-ion batteries (FIBs), which exhibited better framework stability and higher ionic conductivity. Abstract : Aqueous Fe-ion batteries (FIBs) have gradually emerged in recent years due to their inherent merits. Herein, we constructed a Mg-substituted Prussian blue analogue (MgFeHCF) as cathode for FIBs, achieving higher capacity (96 mA h g −1 ) and better stability (70.9% capacity retention over 500 cycles). The Fe-ion storage mechanism was revealed using the in situ XRD technique and DFT calculations were employed to analyse the battery performance.